The Effect of Rare Earth Yttrium and Manganese Additive on Microstructure and Mechanical Properties of Aluminium Alloy - Ibrahim, Muhammad Airisfirdaus; Ahmad, Prof. Madya Dr. Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This research project investigates the impact of rare earth and additive, specifically yttrium (Y) and manganese (Mn), on the microstructure, and mechanical properties of aluminium alloys. The incorporation of rare earth elements into aluminium alloys has been identified as a promising approach to enhance their performance for advanced engineering applications. In this study, various concentrations of yttrium and manganese were added to a base aluminium alloy (Al-Si) to observe the resulting changes in its properties. By examining the alloy's microscopic structure, it was discovered that adding both Yttrium (Y) and Manganese (Mn) not only made the structure finer but also helped spread the intermetallic particles more evenly. These improvements at the microscopic level led to better mechanical properties for the alloys. Hardness measurements also showed a noticeable increase, suggesting enhanced material toughness. Overall, the combination of yttrium and manganese in aluminium alloys significantly improves their microstructure and mechanical strength. This makes them suitable for demanding applications where high performance and durability are crucial, such as in aerospace, automotive, and marine engineering.